TECHNICAL REQUIREMENTS FOR SMALL-SIZED TRACTORS (Multidisciplinary Journal of Science and Technology, 2025)
This article presents information on the development and implementation of a small-sized vegetable-growing tractor designed for use in greenhouses and household plots. The tractor features adjustable wheel track width adaptable to crop row spacing and a high ground clearance suitable for vegetable cultivation conditions.